Silver‐Nanowire/Graphene Stacked Transparent Electrodes and Its Application to Flexible Thin Film Photovoltaic Device - Akasaka, Miho; Noguchi, Masahiko; Kobayashi, Taizo (Electrical engineering in Japan, 2025)
ABSTRACT In this study, silver nanowire covered with graphene (AgNW/Graphene) transparent conducting electrodes (TCE) were developed as bendable TCE instead of conventionally used indium tin oxide (ITO) for flexible photovoltaic applications. CVD‐grown graphene films were transferred from a Cu foil onto a spin‐coated AgNW TCE. AgNW/Graphene TCE exhibited lower electrical resistance than 10 Ω and high optical transmission of approximately 80% at visible wavelengths before and after bending of 20 cycles at a radius of 15 mm. Thermal tolerance of AgNW was drastically improved by protecting silver nanowires with graphene from oxidation at the 300°C air annealing test. ZnMgO/Se thin film photovoltaic devices with AgNW/graphene were successfully demonstrated by insertion of a sol‐gel ZnO buffer layer in order to protect AgNW/graphene from sputtering bombardment.